Science and its times : understanding the social significance of scientific discovery. Volume VIII - Lauer, Josh.; Schlager, Neil, 1966- (Detroit : Gale Group, 2000)
"This series discusses how the major fields of science developed during specific time periods. Each volume focuses on a range of years and includes developments in exploration, life sciences, mathematics, physical sciences, and technology. When the series is completed, the seven volumes will cover 2000 B.C. to the present."--"Outstanding Reference Sources," American Libraries, May 2001.
v. 1. 2000 B.C. to A.D. 699 -- v. 2. 700-1449 -- v. 3. 1450-1699 -- v. 4. 1700-1799 -- v. 5. 1800-1899 -- v. 6. 1900-1949 -- v. 7. 1950-present -- v. 8. Cumulative index.
Includes bibliographical references and indexes.
Keywords: Science -- Social aspects -- History